Strategic Planning of Information Systems and Information Technology for Digital Signature at Balai Sertifikasi Elektronik - Abdul Azzam Ajhari; Albertus E.K. Gunawan; Budi Candra; Bona T. Munthe (International Journal of Data Science, Engineering, and Analytics, 2022)
The COVID-19 pandemic in Indonesia has changed work patterns from those previously based on conventional to digitalization. One of the changes in the work pattern of digitalization is the shift in the behavior of using wet signatures on paper to digital signatures on electronic documents. The use of digital signatures cannot be separated from the strategic planning of information system (IS) and information technology (IT) strategy that refers to business strategies so that companies or agencies can compete. The need for planning in determining business strategy, IS/IT management strategy, and IT strategy before finding future application portfolios. Ward and Peppard were selected and used as a strategic planning method for information systems and information technology in this study. Business strategy can be found using internal and external analysis with strengths, weaknesses, opportunities, and threats (SWOT) with EFAS and IFAS matrix evaluation. The results were achieved in the strategic planning of the appropriate information system and information technology for agencies in achieving their business goals.